Hierarchical Vine‐Tree‐Like Carbon Nanotube Architectures: In‐Situ CVD Self‐Assembly and Their Use as Robust Scaffolds for Lithium‐Sulfur Batteries. (1st September 2014) - Zhao, Meng‐Qiang; Peng, Hong‐Jie; Tian, Gui‐Li; Zhang, Qiang; Huang, Jia‐Qi; Cheng, Xin‐Bing; Tang, Cheng; Wei, Fei
<x xml:space="preserve">Abstract</x> Hierarchical vine‐tree‐like carbon nanotube architectures composed of vine‐like single‐walled carbon nanotubes wrapping around the tree‐like multi‐walled carbon nanotubes are fabricated through in‐situ chemical vapor deposition self‐assembly. The vine‐tree‐like nanoarchitectures exhibit excellent cycling stability and rate performance when employed as the cathode scaffolds for lithium‐sulfur batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>